Teacher’s Experiences with Online Learning in Pulau Sebatik, Sabah - Izzah Afifah Robert; Ahmad Pozin, Mohd Affendi; Nuraini Abdullah; Nur Tasnem Jaaffar (Multidisciplinary Applied Research and Innovation, 2025)
The COVID-19 pandemic has disrupted worldwide education systems, causing many students to turn to online learning as a substitute for traditional classroom instruction. The purpose of this study is to investigate the difficulties encountered by teachers at SMK Wallace Bay in Pulau Sebatik, Sabah, Malaysia while conducting a lesson using an online platform. Qualitative research approaches were used to gather in-depth information from respondents' perspectives based on the realities of teachers' actual experiences with problems while teaching online. The data show that internet access, motivation and moral support, and digital inequality are the major problems that teachers face when conducting online classes. Educational institutions should provide digital devices and comprehensive teacher training to enhance online learning, improve education quality, and ensure equity